Surgical Reconstruction of Mitral-Tricuspid Insufficiency Combined with Biatriomegaly in Marfan Syndrome - Popov, Volodymyr V.; Bolshak, Oleksandr O.; Boukarim, Valery Zh.; Khoroshkovata, Olena V.; Gurtovenko, Oleksii M.; Novikov, Evgen V. (Ukrainian Journal of Cardiovascular Surgery, 2023)
The aim. To analyze the results of introduction of complex reconstruction of the left and right parts of the heart in Marfan syndrome combined with mitral-tricuspid insufficiency, biatriomegaly and left ventriculomegaly. Materials and methods. As an example of this pathology, we present our observation. Female patient T., 24 years old, was examined and treated from 7/27/2022 to 8/17/2022 at the Department of Surgical Treatment of Acquired Heart Diseases of the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine with a diagnosis: Marfan syndrome. Stage IV mitral-tricuspid insufficiency. Biatriomegaly. High pulmonary hypertension. Permanent form of atrial fibrillation (for 10 years, since 2011). IIB heart failure with left ventriculomegaly with reduced left ventricular ejection fraction. NYHA functional class IV+. The patient underwent surgery in the following volume: mitral valve replacement with full preservation of the valve apparatus + tricuspid valve plasty with the imposition of a support ring + triangular plasty of the left atrium with its partial resection + resection of the right atrium. Results. Within 4 months after surgery, echocardiographic parameters showed significant decrease in the volume of the left ventricle, the diameters of both atria. In addition, there was a significant decrease in the level of N-terminal pro-brain natriuretic peptide and manifestations of heart failure. Conclusion. Taking into account the initial serious condition of the patient with Marfan syndrome and advanced mitral-tricuspid heart disease, left ventriculomegaly with a reduced left ventricular ejection fraction, biatriomegaly (left atrium 7.2 cm, right atrium 6.5 cm), permanent form of atrial fibrillation, complex reconstruction of the left and right parts of the heart leads to an improvement in the functional state of the myocardium.